(untitled) (Contemporary Journal of Social Science Review, 2025)
The security landscape of Pakistan is characterized by terrorism, political instability, border disputes, cyber vulnerabilities, and socio-economic factors. This study critiques these dimensions in terms of root causes and implications for national stability along With historical, geopolitical, and contemporary analysis. The investigated results show that internal threats from terrorism, largely by Tehreek-e-Taliban Pakistan (TTP) and porous borders with Afghanistan, Political instability compounds governance gaps that the extremists can exploit and also dilutes effective security responses. Border conflicts with India over Kashmir and Afghanistan also continue to simmer despite physical security measures, such as fencing. Other emerging threats relate to vulnerabilities of critical sectors that impact society. Such sectors, such as the banking and defense industries, are best served through a strong infrastructure in the digital domain and nimble policy frameworks. Gross rates of unemployment and poverty make up some of the major socio-economic factors to radicalization. This is a form of interdependence in matters related to national security and economic stability. CPEC is not only giving regional and international dynamics to Pakistan but also changing Pakistan’s relations with India, Afghanistan, and the world powers by adding new dimensions to the security challenges that Pakistan is facing. The paper aims at bringing out that such considerations would need an integrated approach. Suggestions are holistic approaches in counter-terrorism strategies, all-inclusive socio-economic development, political stability, effective border management through regional cooperation, and proactive cyber security measures. This would mean that the overall security strategy could help Pakistan fight these threats and protect its sovereignty in the framework of regional and global stability. The current analysis acts as a guide for policymakers to take them through the complexity of the security environment to have sustainable progress.